Impact of the COVID-19 Pandemic on Oncology Clinical Research in Latin America (LACOG 0420) - Lara Gongora, AB (2021)
Purpose: COVID-19 has affected cancer care worldwide. Clinical trials are an important alternative for the treatment of oncologic patients, especially in Latin America, where trials can be the only opportunity for some of them to access novel and, sometimes, standard treatments.Methods: This was a cross-sectional study, in which a 22-question survey regarding the impact of the COVID-19 pandemic on oncology clinical trials was sent to 350 representatives of research programs in selected Latin American institutions, members of the Latin American Cooperative Oncology Group.Results: There were 90 research centers participating in the survey, with 70 of them from Brazil. The majority were partly private or fully private (n = 77; 85.6%) and had confirmed COVID-19 cases at the institution (n = 57; 63.3%). Accruals were suspended at least for some studies in 80% (n = 72) of the responses, mostly because of sponsors' decision. Clinical trials' routine was affected by medical visits cancelation, reduction of patients' attendance, reduction of other specialties' availability, and/or alterations on follow-up processes. Formal COVID-19 mitigation policies were adopted in 96.7% of the centers, including remote monitoring and remote site initiation visits, telemedicine visits, reduction of research team workdays or home office, special consent procedures, shipment of oral drugs directly to patients' home, and increase in outpatient diagnostic studies. Importantly, some of these changes were suggested to be part of future oncology clinical trials' routine, particularly the ones regarding remote methods, such as telemedicine. Conclusion: To our knowledge, this was the first survey to evaluate the impact of COVID-19 on Latin American oncology clinical trials. The results are consistent with surveys from other world regions. These findings may endorse improvements in clinical trials' processes and management in the postpandemic period.